VARIATIONS AND DERIVATION OF IDIOMS IN THE KISS NOVEL - Lina Septianasari (UNIVERSITAS MUHAMMADIYAH METRO (MUHAMMADIYAH UNIVERSITY OF METRO), 2018)
Human creativity in using language is incredible. It is reflected through several variations and changes they made in using fixed expressions to express their ideas. One of those is in the way people used idioms. This research discusses about English idioms in The Kiss novel. It aims (1) to describe the forms of idioms used in The Kiss novel and (2) to describe the variations and derivation of idioms used in The Kiss novel. This is a qualitative linguistic research which used novel as the source of the data. English idioms in The Kiss novel become the object of this research. The data here are collected by using reading method. Besides, the collected data then are analyzed by using translational method. The results show that there are 6 types of idioms’ form found in this research, they are: verbal idiom, prepositional phrases, compound, binomial, whole clause or sentence, and ill-formed idiom in which some idioms got lexical variation and derivation on their form. The lexical variation and derivation in idioms’ form can happen as long as the idiomatic meaning of idiom is defensible and can be understood by the language users;